Structure Design and Analysis of High-Voltage Power Supply for ECRH - 王磊 黄懿贽 赵燕平 张健 杨磊 郭文军 (Plasma science & technology, 2014)
In order to develop a high-voltage power supply （HVPS） with high quality parame- ters, not only its electrical circuit but also its structure should be studied in detail. In this paper, the structure design of the collector power supply for gyrotron is discussed first. Then the electri- cal field and potential simulations of its inain devices are analyzed. Finally, relevant calculations and conclusions are given.